Growth and birefringence studies of semi organic non-linear optical LHB single crystal. Issue 1 (17th February 2015) - Jayaramakrishnan, V; Prasanyaa, T; Haris, M; Bhoopathi, G
Abstract: In the last few decades nonlinear optical materials are getting attention in the field of optical data storage, telecommunication, second harmonic generation (SHG) and optical signal processing, etc. In the present work we are reporting the single crystal growth of L-Histidine with hydro-bromic acid. The L-Histidine bromide (LHB) single crystals have been harvested from the solution in a span of 34 days by adopting slow cooling solution growth technique. The grown crystals have been subjected to powder X-ray diffraction studies to identify the cell parameters and structure. The crystalline perfection has been defined by rocking curve (HRXRD) analysis. Optical transmission spectra reveal the optical properties of the grown crystals. The Modified channel spectrum (MCS) method has been adopted for the study of spectral dependence of linear birefringence over the wavelength range 480-620 nm. The second harmonic generation efficiency was tested by using Kurtz and Perry method, keeping KDP as reference.